An affective-cognitive teaching and learning approach for enhanced behavioural engagements among engineering students - Kesot, Mohd Jahaya; Akasah, Zainal Abidin; Alias, Maizam; Lashari, Tahira Anwar (2015)
Promoting students’ engagement has been of great interest to engineering educators as it is associated with better teaching and learning effectiveness. However, students’ engagement is a multifaceted construct comprising the cognitive, affective, and behavioural aspect of engagements which makes it difficult to get a holistic measure of it. Thus, the behavioural engagement alone is often measured as it enables the researcher to investigate outcomes ‘in-action’ and evaluate the individuals’ ability at high-order thinking. The aim of this study is to explore the effect of an integrated affective-cognitive teaching and learning approach on behavioural engagements. The study utilized the quasi-experimental design method with pre- and post-test. The experimental group (n = 36) was taught a course on mechanics of material using the integrated approach while the control group (n = 34) was taught the same course using the conventional method. The results indicate that the integrated affective-cognitive learning approach promotes some types of positive behavioural engagement while suppressing other types of negative engagements. Thus, it was concluded that the integrated teaching and learning approach is effective in promoting positive behavioural engagements among engineering students.